Pembelajaran IPA Berbasis Etnosains Mengenai Proses Fermentasi untuk Menumbuhkan Keterampilan Berpikir kritis - Dea Vira Kusumawati; Laily Rochmawati Listiyani; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2021)
Science learning is related to life and phenomena that occur in the surrounding environment. The learning process will be more meaningful if science is associated with the culture that develops around the community environment and can also be called using an ethnoscience approach. However, science learning in general still does not integrate the culture of both the school environment and the environment of the students. This culture can be learned by learners starting from daily activities such as in the process of making food products, one of which is in the fermentation process in the manufacture of tempeh. This study aims to identify ethnoscience in the fermentation process that can be implemented in learning. Research method used in the form of literature review method. Data collection is done by observation, interview, and analysis of articles or journals. Data analysis techniques are carried out by analyzing the results of observations, interviews, and scientific articles. The results of this literature study prove that ethnoscience-based science learning is important to be implemented in order to foster the critical thinking skills of learners.